THE EFFECT OF PARTICLE SIZE OF VOLCANIC ASH AND PHOSPHATE ROCK IN ANDISOL - Nur Azizah; Mahfud Arifin; Maya Damayani (Jurnal Penelitian Saintek, 2019)
This study was aimed at determining the effect of various particle sizes of volcanic ash and phosphate rock, including normal size (2mm), micron (200 µm) and nano (400 ղ m) on available P, P retention, delta pH and leaf area of tea plant seeds in Ciater PTPN XII Tea Plantation, West Java. The study was carried out in December 2017 until February 2018. The soil analysis was carried out at the Integrated Testing Laboratory, Vegetable Crops Research Institute, Lembang, West Java. The manufacture of micron and nano volcanic ash and phosphate rock particles was carried out at the Nanotechnology and Graphine Laboratory, Mathematics and Science Faculty, Padjadjaran University and at Tekmira Research Center, Bandung. The research design used was a Randomized Block Design (RBD) consisting of 10 treatments of the combination of volcanic ash and phosphate rocks which were repeated three times. The results show that there is a significant effect of volcanic ash and phosphate rocks of normal size to a decrease in P retention of up to 42.87%. The combination of the treatment of normal-sized volcanic ash and nano-sized phosphate rocks has a significant effect on the total leaf area of the Gambung 7 clone plant, but it did not significantly affect the available P and delta pH.PENGARUH UKURAN PARTIKEL ABU VULKANIK DAN BATUAN FOSFAT PADA ANDISOLPenelitian ini bertujuan untuk mengetahui pengaruh pemberian berbagai ukuran partikel abu vulkanik dan batuan fosfat, meliputi ukuran normal (2mm), mikron (200 µm) dan nano (400 ղm) terhadap P tersedia, retensi P, delta pH dan luas daun bibit tanaman teh di Perkebunan Teh PTPN XII Ciater, Jawa Barat. Penelitian lapangan dilaksanakan pada Desember 2017 sampai Februari 2018. Analisis tanah dilakukan di Laboratorium Penguji Terpadu, Balai Penelitian Tanaman Sayuran, Lembang, Jawa Barat. Pembuatan partikel mikron dan nano abu vulkanik dan batuan fosfat dilakukan di Laboratorium Nanoteknologi dan Graphine, Fakultas MIPA, Universitas Padjadjaran dan di Puslitbang Tekmira, Bandung. Rancangan penelitian yang digunakan adalah Rancangan Acak Kelompok (RAK) yang terdiri atas 10 perlakuan kombinasi ukuran abu vulkanik dan batuan fosfat yang diulang sebanyak tiga kali. Hasil penelitian ini menunjukkan bahwa terdapat pengaruh nyata pemberian abu vulkanik dan batuan fosfat yang berukuran normal terhadap penurunan retensi P hingga 42,87%. Kombinasi perlakuan abu vulkanik berukuran normal dan batuan fosfat berukuran nano berpengaruh nyata terhadap total luas daun tanaman teh klon Gambung 7, tetapi tidak berpengaruh nyata terhadap P tersedia dan delta pH.